CLINICAL APPLICATION OF ICD-11 AND ITS UNDERSTANDING AMONG THE PSYCHIATRISTS AND POST GRADUATE PSYCHIATRIC RESIDENTS OF PAKISTAN - Khan, Muhammad Nasar Sayeed; Irshad, Mahnoor; Nasar, Amina (Journal of Pakistan Psychiatric Society, 2022)
Objectives: To find out the problems associated with the clinical utilization of ICD-11 by the psychiatrists of Pakistan. To understand the basic description of its utilization in clinical practice. Study design: It is a cross-sectional descriptive study. Place and duration of study: The study was conducted through an online survey which was circulated to the psychiatrists across country. Subjects and methods: A sample size of 130 psychiatrists including the post graduate residents responded to the e-mail and WhatsApp messages. The survey was on Google Docs, and it was an online survey with responses of “yes, no and don’t know”. The ethical approval for the survey was taken from Pakistan psychiatric research centre, fountain house Lahore, Pakistan. Results: Out of 130 psychiatrists, 65.4% were the residents who heard about ICD-11 mostly from academic activity conducted by the authors. 48.5% of psychiatrists believe that it is difficult to adjust with the new classification system. Conclusion: ICD-11 is a new classification system. It requires training from the seniors and workshops related to its utility through the online mortality and morbidity statistics by WHO across various countries.